Encyclopedia of Life Sciences 2020
DOI: 10.1002/9780470015902.a0029196
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses: Primary and Secondary

Abstract: Immune responses to antigens may be categorised as primary or secondary responses. The primary immune response to antigen occurs on the first occasion it is encountered. This response can take up to 14 days to resolve and leads to the generation of memory cells with a high specificity for the inducing antigen. The humoral response, mediated by B cells with the help of T cells, produces high‐affinity and antigen‐specific antibodies. In contrast, the CD8 T‐cell response leads to the generation of large numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…During primary infection, a pathogen spreads too rapidly, does too much damage and proliferates to a level sufficient to elicit an adaptive immune response and then stimulates the production of antibodies and effector T cells that in turn produce high levels of cytokines to eliminate the pathogen from the body, while in a secondary infection to the same antigen, the antibody and memory T cells remaining in an immunized individual prevent the activation of naive B and T cells but memory cells are rapidly activated and can respond much more quickly and effective than the primary response [ 78 ]. The herein results are in agreement with [ 79 ] who revealed that the transcripts of the pro-inflammatory cytokines IFN- γ, IL-1β and IL-6 were increased following primary infection, while their expression was slightly changed following secondary infection in E. tenella -infected chickens. The E. tenella infection caused upregulation in the pro-inflammatory cytokines; IFN- γ, IL-1β and IL-6 in chickens caecal tissue [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…During primary infection, a pathogen spreads too rapidly, does too much damage and proliferates to a level sufficient to elicit an adaptive immune response and then stimulates the production of antibodies and effector T cells that in turn produce high levels of cytokines to eliminate the pathogen from the body, while in a secondary infection to the same antigen, the antibody and memory T cells remaining in an immunized individual prevent the activation of naive B and T cells but memory cells are rapidly activated and can respond much more quickly and effective than the primary response [ 78 ]. The herein results are in agreement with [ 79 ] who revealed that the transcripts of the pro-inflammatory cytokines IFN- γ, IL-1β and IL-6 were increased following primary infection, while their expression was slightly changed following secondary infection in E. tenella -infected chickens. The E. tenella infection caused upregulation in the pro-inflammatory cytokines; IFN- γ, IL-1β and IL-6 in chickens caecal tissue [ 80 ].…”
Section: Discussionsupporting
confidence: 93%
“…TGF-β4, in particular, has been found to increase in chickens after coccidian infection [ 104 ]. Following primary E. tenella infection, the level of TGF-β4 expression was increased, while it was slightly changed following secondary infection [ 79 ]. The expression of TGF-β4 was increased in coccidian-infected chickens with E. acervuline [ 105 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Together, these results show that TmEnc has immunogenic properties and triggers a classical adaptive immune response, wherein IgMs are initially produced by the body before isotype switching to high‐affinity IgGs occurs, a process that takes approximately fourteen days to resolve. [ 39,40 ] It is important to note that TmEnc‐specific antibody generation implies the occurrence of an inflammatory response, which was most likely to have dissipated by the time pro‐inflammatory cytokines were first measured in serum one day after TmEnc administration. Other IV‐injected PNCs have also been reported to induce the production of PNC‐specific antibodies, and this immune response plays a key role in their elimination from the body.…”
Section: Resultsmentioning
confidence: 99%
“…If the organism is re-exposed to antigen, a secondary immune response is stimulated by T cell proliferation and/or secondary antibody production by B cells. 19 During primary response, activation, proliferation and differentiation into a T cell-specific to this antigen ensue after a successful recognition of the antigen by a helper T cell. These T cells stimulate naïve B cells, which then migrate to germinal centres and differentiate into antigen-specific plasma cells and memory B cells.…”
Section: Immunological Rolementioning
confidence: 99%
“…If the encountered antigen is novel, the primary immune response is activated. If the organism is re-exposed to antigen, a secondary immune response is stimulated by T cell proliferation and/or secondary antibody production by B cells 19. During primary response, activation, proliferation and differentiation into a T cell-specific to this antigen ensue after a successful recognition of the antigen by a helper T cell.…”
Section: Immunological Rolementioning
confidence: 99%